Sapiens : a graphic history. Volume two, The pillars of civilization - Harari, Yuval N.; Harari, Yuval N.; Vandermeulen, David, 1968-; Vandermeulen, David, 1968-; Casanave, Daniel (Harper Perennial, 2021)
In the second "Sapiens" volume, Yuval Noah Harari tells the story of how we took over the world; how an unlikely marriage between a god and a bureaucrat created the first empires; and how war, famine, disease, and inequality became a part of the human condition. The origins of modern farming are introduced through Elizabethan tragedy, the changing fortunes of domesticated plants and animals are tracked in the columns of the Daily Business News, and the story of urbanization is told as a travel brochure offering discount journeys to ancient Babylon and China.